Teaching literacy to learners with dyslexia a multisensory approach - Kelly, Kathleen; Phillips, Sylvia (London SAGE, 2022)
This bestselling text offers theoretical detail and depth alongside a programme of activities to implement in practice which can improve literacy levels and support children with dyslexia"--
Keywords: Dyslexic children -- Education -- Great Britain; Literacy -- Study and teaching -- Great Britain; English language -- Study and teaching -- Great Britain -- Activity programs; Children with disabilities -- Education -- Great Britain; Literacy -- Study and teaching -- Activity programs; English language -- Study and teaching -- Activity programs